THE KINDERGARTEN INTERIOR AS AN IMPORTANT FACTOR FOR THE HEALTHY DEVELOPMENT OF PRESCHOOL CHILDREN (Innovation in Woodworking Industry and Engineering design, 2026)
An important factor for the healthy growth and development of children is the proper organization of interior space and the use of adequate equipment tailored to their age. Analyzing psycho-physical activities of children in kindergartens and the functions they perform during the day, an environment should be designed to fit their social, cognitive, psycho-physical and other developing needs. Organization of environment or design of kindergarten playrooms is the key factor as well as furniture design. The paper presents the environment of 27 public kindergartens in towns Skopje, Zagreb and Sofia and analyses current state of interior and furniture design in their playrooms. The new suggestions based on observed environments are given.